"Elaboración de una guía turística de los principales atractivos para la Provincia Santo Domingo de los Tsáchilas, año 2020" - Torres Beltrán, Wendy Evelyn (2020)
The present investigation; It was carried out with the purpose of preparing a tourist guide of the main attractions for the province of Santo Domingo de los Tsáchilas, the philosophical approach was made through focus groups, according to the existing problems in the province Tsáchila, the Provincial GAD of the study site, raised the need to technically structure this research, to later implement it. The main and complementary information systematization was developed in relation to the areas of the tourist system such as: natural and cultural attractions, identifying their current states. In the inventory of attractions there are 7 natural attractions and 3 of cultural manifestations corresponding to hierarchies II, III, IV. They have the necessary potential for sustainable tourism development in the area. Field visits were also carried out, surveys were applied to the population and the tourist guide was even shared for its approval, which contains important data such as; history, symbols, general data, tourist map, information on how to get to the province, complementary services, traditions and celebrations, calendar of festivities, typical gastronomy; detailed information such as: schedules, cost of entry, activities and recommendations, of each of the attractions; myths and legends, tourist establishments, telephone numbers that will be very useful, health centers, banks, emergencies among others, this information will be very useful for tourists to enjoy their stay in each site they visit, in order to promote the development of tourist activities, in addition this document will be easy to interpret, it is intended to position the Tsáchila province as a wonderful tourist destination of Nature, Adventure and Cultural. It is concluded that the province has a great tourist potential and this research has the precise bases to contribute to the socio-economic development of the population and the province. KEYWORDS Tourist guide, tourist attractions, tourist activities, natural attractions, cultural attractions